KREATIVITAS PERNAK PERNIK MASKER UPAYA MENCUKUPI KEBUTUHAN EKONOMI DI MASA PANDEMI COVID 19 DI DESA GUNUNG KELAMBU KABUPATEN TAPANULI TENGAH - Sipahutar, Hadijah; Hadia Lubis, Rifka; Nur Simamora, Fauziah (COVIT (Community Service of Tambusai), 2022)
The pandemic is indeed scary but also a challenge. In the midst of the threat of a pandemic, people must rise up so that there is no dilemma; just staying at home ends up starving, going out of the house is threatened with Covid-19. By adding knick-knacks in the mask without having to reduce the main function to prevent the transmission of Covid-19 so that consumers will later be interested in the market share. creativity in making masks with added knick-knacks such as adding crystal sequin stones, ribbons and others make it unique. With the implementation of this Community Service, it is hoped that the women of the Gunung Kelambu village community can increase their knowledge about the creativity of making masks and promising business opportunities to be applied in daily activities. The only chance to survive and continue this life is to open up new opportunities. In addition to the motivation to unite, remind each other of our abilities, together to rebuild a good life in the midst of a pandemic is very important. In a slumped situation like today, everyone must remind each other that Bali will survive in any situation. Even in a pandemic situation like today. The most important thing here is the support from the local government to support and support them, provide space for creativity for their creative work, open space for distribution or distribution of their work, encouraging that the people of Gunung Kelambu village can overcome this slumping situation. Keywords: Knick-knacks, Economy, Covid 19 Pandemic